2022
DOI: 10.1021/acsinfecdis.1c00600
|View full text |Cite
|
Sign up to set email alerts
|

A Recombinant Subunit Vaccine Induces a Potent, Broadly Neutralizing, and Durable Antibody Response in Macaques against the SARS-CoV-2 P.1 (Gamma) Variant

Abstract: FDA-approved and emergency use-authorized vaccines using new mRNA and viral-vector technology are highly effective in preventing moderate to severe disease; however, information on their long-term efficacy and protective breadth against severe acute respiratory syndrome coronavirus 2 variants of concern (VOCs) is currently scarce. Here, we describe the durability and broad-spectrum VOC immunity of a prefusion-stabilized spike (S) protein adjuvanted with liquid or lyophilized CoVaccine HT in cynomolgus macaques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…To determine dose dependent inhibition of SARS-CoV-2 by cysteamine HCl, Vero-TMPRSS2 was selected, because this cell line is known to be highly permissible to both wild type and the six variants tested in this study. Moreover, these viruses were shown to produce defined plaques when assayed in this cell line (18). As described in the Materials and Method section, SARS-CoV-2 was pre-incubated with different concentrations of cysteamine HCl at 37°C in 5% CO2 for 120 min and the mixture was then added to Vero-TMPRSS2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…To determine dose dependent inhibition of SARS-CoV-2 by cysteamine HCl, Vero-TMPRSS2 was selected, because this cell line is known to be highly permissible to both wild type and the six variants tested in this study. Moreover, these viruses were shown to produce defined plaques when assayed in this cell line (18). As described in the Materials and Method section, SARS-CoV-2 was pre-incubated with different concentrations of cysteamine HCl at 37°C in 5% CO2 for 120 min and the mixture was then added to Vero-TMPRSS2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Interpolated IgG concentrations were calculated as previously described [11]. Briefly, SARS-CoV-2 spike reactive IgG was purified by protein A and spike-protein affinity chromatography from pooled sera of humans immunized with SARS-CoV-2 mRNA vaccines.…”
Section: Microsphere Immunoassay (Mia)mentioning
confidence: 99%
“…To determine which samples had a measurable IgG concentration to the Wu-1 Trimer, samples were analyzed simultaneously with a standard curve derived from polyclonal IgG purified from vaccinated individuals [11]. Individual IgG concentrations were calculated by interpolating the raw MFI values of the test samples on a standard curve established using purified polyclonal human anti-Wuhan Hu-1 antibodies.…”
Section: Sars-cov-2 Spike (Wuhan Hu-1 Strain) Specific Igg Concentrat...mentioning
confidence: 99%
See 1 more Smart Citation
“…To et al (2022) demonstrated that immunization with both 5 and 25 g doses of S significantly lowered Gamma viral load in both the upper and lower respiratory tracts, signifying a reduced likelihood of viral transmission, even in macaques with minor symptoms [212]. There has been little research on the viral load of the Gamma variant.…”
Section: Viral Loadmentioning
confidence: 99%